The Significance of Effective Labour Inspectoratesfor Cross-border Labour Mobility - Ryszka, Joanna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
Efficiently functioning labour inspectorates play a key role for both fair mobility and the protection of workers’ rights. They contribute, for example, to combating and eliminat-ing hazardous working conditions, and ensuring that remuneration and social insurance premiums are actually paid. This is significant in the context of the posting of workers in the framework of the provision of services. Establishing the liability regarding compli-ance with the occupational health and safety regulations is causing serious practical dif-ficulties. Therefore, it is important above all to identify initiatives undertaken at the EU level designed to enhance cooperation of national labour inspectors in this field. It is also important to carry out an assessment whether they work efficiently, require systematis-ing, or perhaps it is necessary to undertake more formalised initiatives, e.g. in the form of a new EU institution.